Upaya Peningkatan Nilai Overall Equipment Effectiveness pada CV Bintang Lima Plastindo - Stefando Gabriel Angrianto; Felecia Felecia (Jurnal Titra, 2020)
CV Bintang Lima Plastindo manufactured plastic pallets and plastic ropes. Currently, the company did not have a planned maintenance schedule. Breakdown maintenance in the company required more time because operators are not ready to fix the problems. Longer machine downtime affects machine performance, which can be seen in the OEE score. Previous company OEE score is 56,56%, which is far below the ideal standard. This research conducted to design a suitable maintenance schedule to improve the OEE score. The maintenance schedule is designed based on the mean time to failure (MTTF) of every breakdown occurs, and real condition in the factory. A new planned maintenance schedule is simulated and compared with the previous condition. The result shows that OEE is improved by 0.73% and can increase company income by IDR 1.098.412.984,60.